How to manage land use conflict between ecosystem and sustainable energy for low carbon transition?: Net present value analysis for ecosystem service and energy supply - Kim, Jiwon; Park, Eunbeen; Song, Cholho; Hong, Mina; Jo, Hyun-Woo; Lee, Woo-Kyun (Frontiers in Environmental Science, 2022)
Solar energy generation has become one of the most popular renewable energy sources for achieving global carbon neutrality. This transition to land-intensive energy generates inevitable land use conflicts with existing land cover, such as forest or agricultural land. South Korea is one of the countries currently experiencing conflicts in land use between ecosystems, food and energy. In addition, various land use problems occur, such as deforestation due to developments and an increase in idle agricultural land due to a decrease in the labor force. Thus, it is important to establish future land use policies that consider these issues. This study conducted a net present value (NPV) analysis for solving land use conflict by comparing monetary value according to different land use cases. Two land use scenarios were investigated: 1) land cover maintained (forest or agricultural land) and 2) land use change for solar energy generation. These two scenarios were compared in the target areas selected in this study to determine the criteria for the solar energy generation site. The economic values from Scenario 1 were calculated primarily using ecosystem services assessment and market value, and those of Scenario 2 were calculated based on statistical data. The total suitable area for solar energy generation in Korea was 551,393 ha. As results, the NPV analysis in forests showed that the NPV of forest ecosystem services was higher than that of solar energy generation in forest. In the case of idle agricultural land, agriculture caused a continuous deficit owing to carbon emissions, and accordingly, the carbon reduction effect through solar energy generation had a greater value than agricultural activities. This study attempted to resolve land use conflict by considering carbon neutrality through comparing economic values and introducing ecosystem services assessment and carbon credit price in the process of the analysis.